Cobalt-Catalyzed CH Cyanation of Arenes and Heteroarenes - Li, Jie; Ackermann, Lutz (Angewandte Chemie International Edition, 2015)
Carboxylate assistance proved to be the key for the success of efficient cobalt(III)‐catalyzed CH cyanations. Thus, an in situ generated cationic cobalt complex was identified as a versatile catalyst for the site‐selective synthesis of various aromatic and heteroaromatic nitriles with ample substrate scope. As directed: The title reactions were accomplished with in situ generated cobalt(III) carboxylate complexes for highly efficient CH activations. The direct cyanation proved viable with removable directing groups and displayed a broad substrate scope and mild reaction conditions.